الإجازة العلمية التي منحها الشيخ توفيق البرزنجي لملا محمود المورياسي دراسة وتحقيق - كريم, حسين حسن (Sulaimani Journal for Humanities, 2022)
The scientific certificate that muslim scientists gave to those students who have done all educational stages and received good capabilities was very valuable to them. They did not accept uncapable students, so gaining that license has gone gradually and level after level till the era of the Prophet, peace be upon him. I would like to do a scientific research about the process of recovering the timeline of those muslim scientists who gave students license in some of the religious schools in South Kurdistan. This research focuses on recovering the license of Mula Sheikh Tawfiq Shiekh Abdul-Rahman Al Barzanji to his student Mula Mahmood Kzlli Moryasi and comparing it to other licenses which were given by other Kurdish scientists, but we figure out that they are all the same. By writing this paper, I acknowledge that the timeline may be changed somewhere, such as it mentioned that Fakhradeen Al-Razi had been certified by Imam Al-Ghazali, which is not a fact as Al-Razi was born 40 years after Al-Ghazali’s death. Readers would face some facts that we discover and recover.